2010
DOI: 10.4141/cjas10002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity in four Canadian swine breeds using pedigree data

Abstract: Melka, M. G. and Schenkel, F. 2010. Analysis of genetic diversity in four Canadian swine breeds using pedigree data. Can. J. Anim. Sci. 90: 331Á340. Conservation of animal genetic resources entails judicious assessment of genetic diversity as a first step. The objective of this study was to analyze the trend of within-breed genetic diversity and identify major causes of loss of genetic diversity in four swine breeds based on pedigree data. Pedigree files from Duroc (DC), Hampshire (HP), Lacombe (LC) and Landra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 37 publications
7
56
3
Order By: Relevance
“…In any case, the general scenario of the Gochu Asturcelta pig breed can hardly be compared with others in the literature. Indeed, pedigree depth is substantially lower than the depths reported for the well-established commercial pig breeds of Canada and the United States (Melka and Schenkel 2010;Welsh et al 2010) which included, in general, more than 11 complete generation equivalents. Nevertheless, the mean inbreeding in the breed is up to seven-fold higher than that reported for these American pig populations, ranging from 0.032 to 0.078.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In any case, the general scenario of the Gochu Asturcelta pig breed can hardly be compared with others in the literature. Indeed, pedigree depth is substantially lower than the depths reported for the well-established commercial pig breeds of Canada and the United States (Melka and Schenkel 2010;Welsh et al 2010) which included, in general, more than 11 complete generation equivalents. Nevertheless, the mean inbreeding in the breed is up to seven-fold higher than that reported for these American pig populations, ranging from 0.032 to 0.078.…”
Section: Discussionmentioning
confidence: 74%
“…Average generation interval computed for Gochu Asturcelta (1.8 years) is consistently the same as the others previously reported in the literature for non-endangered pig breeds. Melka and Schenkel (2010) reported generation intervals of 1.6 and 1.7 years for Canadian Duroc and Landrace, respectively; Welsh et al (2010), analyzing the pedigree of five United States pig breeds, reported generations intervals ranging from 1.7 (Berkshire) to 2.2 (Yorkshire) years; Tang et al (2013), in three cosmopolitan pig breeds imported into China, reported generation intervals ranging between 1.8 and 1.9 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the upper limit being above 50, the lower limit is well below the recommended threshold value, supporting the recommendation to increase the effective population size. In an analysis of four Canadian pig breeds Melka and Schenkel (2010) found small effective population sizes for the Hampshire (14) and Lacombe (22) breeds and emphasized that these breeds should be the subjects of conservation practices, as a small effective population size will lead to lower genetic diversity in the future. These findings highlight the importance of larger effective population sizes for the maintenance of genetic variability within a breed.…”
Section: Resultsmentioning
confidence: 99%
“…Barros et al (2011), evaluating the Brazilian goat breed Marota, found the effective number of founders and ancestors was 48 animals and the number of ancestors that explained 50 % of population variability was 22. In an analysis of four Canadian pig breeds, Melka and Schenkel (2010) determined the effective number of founders to be 275, 11, 56 and 54 for the Duroc, Hampshire, Lacombe and Landrace breeds, respectively. In addition, the number of ancestors that explained 50 % of the gene pool were especially low for the Hampshire (4 animals) and Lacombe (7 animals) breeds.…”
Section: Resultsmentioning
confidence: 99%